1996
DOI: 10.1152/ajpheart.1996.270.1.h160
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced detachment of adherent platelets from fibrinogen-coated surface

Abstract: A study of the shear forces under which adherent platelets of different morphologies can be detached from surfaces was carried out using a newly designed tapered flow chamber, which covered the entire shear range of physiological circulation. Platelets that naturally settled on a fibrinogen-coated surface were exposed to shear flow and were subsequently processed for scanning electron microscopic observation. We found that 1) the density of platelets remaining after flow exposure decreased with local shear str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…In addition, the procedure for fibrin immobilization used a silane coupling agent associated with polyglutaraldehyde. Thus, in contrast to meshworks prepared by spraying or adsorption of fibrinogen (17,11,18), where immobilization of fibrinogen takes place by nonspecific physisorption resulting in conformational changes (48,49), the conformation of fibrinogen was preseved as indicated by immunological studies (25,29), and a firm attachment through covalent interactions was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the procedure for fibrin immobilization used a silane coupling agent associated with polyglutaraldehyde. Thus, in contrast to meshworks prepared by spraying or adsorption of fibrinogen (17,11,18), where immobilization of fibrinogen takes place by nonspecific physisorption resulting in conformational changes (48,49), the conformation of fibrinogen was preseved as indicated by immunological studies (25,29), and a firm attachment through covalent interactions was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…This simplified approach has been followed recently by three different teams (16)(17)(18). However, their studies have been focused mainly on biochemical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the flow was further increased to simulate the conditions of coronary arteries at 3.2 N/m 2 , platelet numbers at hydrophilic surfaces were significantly reduced as compared with hydrophobic surfaces [167]. These results strongly suggest detachment of platelets from hydrophilic surfaces, which can be explained by the small contact area of platelets [168]. Furthermore, the platelets attached to hydrophilic surfaces remain spherical and thus experience higher shear forces.…”
Section: Biomaterials Surface Characteristics In Relation To Haemocmentioning
confidence: 99%
“…In contrast, platelets on hydrophobic materials can withstand high shear forces due to strong contact and complete spreading of platelets. When examined with scanning electron microscopy, the platelets on hydrophobic surfaces were indeed more extended like a pancake than on similar material with hydrophilic characteristics [168]. It can be concluded that under conditions of arterial flow, especially at hydrophilic surfaces, less platelets adhere after 15 min due to detachment [169].…”
Section: Biomaterials Surface Characteristics In Relation To Haemocmentioning
confidence: 99%
“…Further, the embolization of single platelets has been reported to be a strong function of surface chemistry and shear rate. 27,49 Thus, for this model, an exponential single-platelet embolization term was included. Thrombus embolization is also well documented and has been shown 19 to be cyclic and significant.…”
Section: Species (Units)mentioning
confidence: 99%